The acoustic emission transducer calibration using spark method - F. DUŠEK; C. SEIDL; J. SIEDLACZEK; S. PILECKI (Archives of Acoustics)
The present paper deals with the problem of frequency characteristics and of the sensitivity of acoustic emission (AE) transducers. Basing on a theoretical analysis of possible calibration methods of AE transducers, the method of random noise was chosen using the spark impact as the exciting signal source. The theoretical fundaments of the spark calibration method given in the present work were verified experimentally. On these results, the experimental device was designed and built in the Institute of Physical Metallurgy, Czechoslovak Academy of Sciences in Brno. It is presented in this paper. Estimated by this device characteristics of AE transducers made by META, Prague, Czechoslovakia and by UNIPAN, Warsaw, Poland, are presented.